2019
DOI: 10.1149/2.0211911jss
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Method for Adhesion Forces between Polyvinyl Acetal Brushes and Flat Surfaces

Abstract: The adhesion force between two materials is a key factor in surface cleaning. In this study, we developed a method for measuring adhesion forces between polyvinyl acetal (PVA) brushes and several test surfaces to understand the brushes’ adhesion characteristics. We utilized both the viscoelastic properties of PVA brushes and a high-response load cell to evaluate the adhesion forces of the compressed brushes on a flat surface. The results of the study showed that the adhesion forces increased with increased con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This difference in contact area for both types of brushes can significantly affect the scrubbing process by changing the friction forces generated during post-CMP cleaning as a higher contact area provides a higher friction force. 15,16 Effect of skin layer on brush contamination.-The effect of the skin layer on the brush scrubbing process using ceria slurries is shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference in contact area for both types of brushes can significantly affect the scrubbing process by changing the friction forces generated during post-CMP cleaning as a higher contact area provides a higher friction force. 15,16 Effect of skin layer on brush contamination.-The effect of the skin layer on the brush scrubbing process using ceria slurries is shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…Yamada et al reported higher frictional forces generated during brush scrubbing for brushes with skin layer that leads to higher cleaning efficiencies. 15 Hence, the presence of the skin layer resulted in higher drag forces during brush scrubbing due to larger contact areas that subsequently provide higher cleaning performance than brushes without skin layers. Therefore, the presence of the skin layer leads to higher abrasive contamination that results in higher cross-contamination but provides a higher cleaning performance due to larger contact areas and higher frictional forces generated during scrubbing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brush scrubbing continues to be widely used in advanced-node post-CMP cleaning applications to remove contaminants (e.g., trace metals, organic slurry residues, polishing pad debris, and abrasive particles) from the wafer surface. 17,18 It has been reported that abrasive particle removal mainly results from direct contact between a soft polyvinyl alcohol (PVA) brush and the wafer surface in which asperities atop nodules engulf the particles while the rotating motion of the brush and the wafer, as well as the cleaning fluid at the surface, dislodge and carry the particles away from the wafer. Among many factors, the effectiveness of brush scrubbing depends on the shear force (SF) present in the brush-solution-wafer interface as well as the kinematics of the PVA brush scrubber.…”
mentioning
confidence: 99%